Acute Effects of Different Formats of Small-Sided and Conditioned Handball Games on Heart Rate Responses in Female Students During PE Classes - Filipe Manuel Clemente; Rúben Filipe Rocha; Fernando Manuel Lourenço Martins; Rui Sousa Mendes (MDPI AG, 2014)
The aim of this study was to analyze the impact of different formats (2-a-side, 3-a-side and 4-a-side) on heart rate responses of female students during small-sided and conditioned handball games. The heart rate responses were measured using heart rate monitors during physical education classes. Eight female students participated in the study (15 ± 0.0 years). The one-way ANOVA showed statistical differences with moderate effect between the three different formats (F(2, 1674) = 86.538; p-value ˂ 0.001;  = 0.094; Power = 1.0). The results showed that smaller formats (2-a-side and 3-a-side) increased the heart rate responses of female students during small-sided and conditioned handball games during physical education (PE) classes. The results also suggested that 2-a-side games can be used for anaerobic workouts and the 3-a-side and 4-a-side games can be better used to reach lactate-threshold and for aerobic workouts of high intensity.